The effects of rural development on main sources of farm households. Issue 1 (November 2021) - Sumaryanto,; Susilowati, S H; Saptana,; Ashari,; Suryani, E; Suryadi, M
Abstract: In line with the development of the rural villages, rural employment changes. Consequently, the job opportunities of some farmers will also change. This study aims to estimate the effect of rural development and some other factors on the primary source of household income of farmers in several agroecosystems. The data analyzed were the 2013 Agricultural Census, Village Potential and "PATANAS" data. The results showed that farmers' opportunity of leaving agriculture as the main source of household income increased if cultivated land was smaller and the inequality of landholding in the village increased. In the set of variables that determine rural development, improvements in the dimensions of basic services and basic infrastructure of non-accessibility/transportation positively affect the opportunities of farmers' households to make non-agricultural work as their source of income. Improvements in the accessibility/transportation dimension, on the other hand, strengthen the ability of farm households to rely on agriculture as a source of household income. Based on the research results, increasing the agricultural sector as a significant contributor to farmer household income can be achieved by increasing accessibility/transportation facilities and improving the distribution of cultivated land.